PANDANGAN DUNIA GHASSAN KANAFANI DALAM CERPEN “ARDHU AL-BURTUQOL AL-HAZIIN” - Saila Fadhila Ulfa (An-Nahdah Al-'Arabiyah is published by Department of Arabic Language and Literature in cooperation with The Center for Research and Community Service (LP2M), 2023)
This research aims to reveal the author's worldview, namely Ghassan Kanafani as a collective subject in his short story entitled